Endoprothetischer Ersatz des oberen Sprunggelenks bei Patienten mit Gerinnungsstörungen = Total ankle replacement in patients with bleeding disorders - Barg, Alexej; Schneider, Stefan W. (Der Orthopäde, 2015)
Background: Total ankle replacement (TAR) is a well-accepted treatment option in patients with end-stage ankle osteoarthritis. However, published literature on patients with bleeding disorders treated with TAR is limited. Therefore, we carried out this prospective study to analyze mid-term postoperative results in patients with bleeding disorders treated by TAR.Methods: A total of 34 patients with end-stage ankle osteoarthritis—14 patients with hemophilia type A and 20 patients with von Willebrand disease (VWD)—treated by TAR were included in this prospective study. The mean age of patients was 46.0 ± 9.0 years. Intraoperative and postoperative complications were recorded. The postoperative pain relief and functional results including range of motion (ROM) and American Orthopaedic Foot and Ankle Society (AOFAS) hindfoot score were assessed after a mean follow-up of 6.3 ± 3.4 years. Additionally, the quality of life was analyzed using the SF-36 questionnaire. The alignment of prosthesis components was assessed using weight-bearing conventional radiographs. The results were compared with those obtained in the control group, including 72 and 33 patients with post-traumatic and rheumatoid ankle osteoarthritis respectively.ResultsOne patient sustained an intraoperative medial malleolar fracture. In total, three revision surgeries were necessary in our patient cohort. There was significant pain relief from 8.2 ± 0.8 to 0.9 ± 1.0, as assessed using a visual analog scale. All categories of the SF-36 score showed significant improvement. The average ROM increased from 20.1° ± 6.9° to 27.5° ± 7.4°. The AOFAS hindfoot score increased from 34.5 ± 10.0 to 82.4 ± 10.2 of a maximum of 100 points. Radiographic assessment showed the neutral alignment of prosthesis components in all patients. The postoperative clinical and radiographic outcomes were comparable in both patients with hemophilia and those with VWD. Patients with bleeding disorders had significantly higher pain relief and significantly lower ROM than the patients in the control group with ankle osteoarthritis of post-traumatic or rheumatoid etiology.Conclusion: Our prospective study revealed encouraging mid-term outcomes after TAR in patients with bleeding disorders. However, this surgery should be limited to highly experienced foot and ankle surgeons. Furthermore, this patient cohort requires a multidisciplinary approach to ensure a good outcome.
Gesehen am 03.12.2018